Analisis Yuridis terhadap Tindak Pidana Narkotika dalam Perspektif Hukum Pidana Khusus - Nur Shaella Maharani; Felysha Azwa Tasbihta Surbakti; Annisa Febianna Manurung; Muhammad Oriza Arifin (YASIN, 2026)
The increase in narcotics crimes in Indonesia poses a serious threat to society, state security, and law enforcement because these crimes are categorized as extraordinary crimes that are organized, transnational, and have broad impacts on public health, social life, and the economy. This study aims to analyze the legal regulation of narcotics crimes, examine the position of evidence in narcotics cases, and review the application of criminal law from the perspective of special criminal law in Indonesia. This study used a normative juridical method with a qualitative approach through library research by examining laws and regulations, legal theories, journals, books, and court decisions related to narcotics crimes. The results showed that evidence has an important position in proving narcotics crimes because it serves to prove the occurrence of a criminal offense and to link the defendant to the charged criminal act. The process of seizure and forensic laboratory examination of evidence also affects the validity of proof in court proceedings. In addition, judges consider the type, quantity, and relevance of evidence in determining criminal sanctions against defendants. The conclusion of this study affirms that handling evidence professionally and in accordance with legal procedures is an important aspect of realizing legal certainty and justice in narcotics crime cases. These findings contribute to the development of studies on special criminal law and have practical implications for law enforcement officials in strengthening the governance of evidence in narcotics cases.